Final Year Nursing Students’ Knowledge and Self-perceived Competency, in Urinary Catheterisation and Catheter Care Skills - Lonsdale, Victoria (2014)
Abstract Background This study explored final year student nurses’ knowledge and confidence of urinary catheterisation and catheter care skills. Catheter associated urinary tract infection has a personal burden for patients, but the economic implications for the National Health Service are also extensive. Catheterisation knowledge has been found to be poor in post registration nurses, suggesting that this may also be true of student nurses. This study was conducted to inform current pre-registration clinical skill training, education and examination techniques. Methods A questionnaire method was used with 145 final year student nurses at the University of Nottingham participating. Students were from BSc, Diploma and MNurSci courses, studying adult, child or mental health nursing. Questions asked explored previous training, perceived confidence, extra learning accessed, students’ thoughts on a catheterisation examination and a knowledge ‘test’ on catheterisation and catheter care. Results The study identified that students’ lack of knowledge of urinary catheterisation is considerable. 91.7% of all students scored less than half on the catheterisation knowledge sub-section. Evaluation of current training methods and student confidence highlighted that student confidence is very low, and most students felt they had not received enough education in this skill (89.0%). No correlation was found between confidence and competency, as students who scored their confidence highly did not necessarily score highly on the knowledge section. The majority of students think that a practical examination in catheterisation would improve their competency (73.8%).